Efficacy of spinetoram and flupyradifurone against bruchid on blackgram (Vigna mungo) under storage conditions - NELAGUNDA, AKSHATA; R, SIDDARAJU; MURTHY, PARASHIVA; C, MANJANAIK; T V, KRISHNA; B L, JYOTHI; MOPURI, RAMGOPAL (The Indian Journal of Agricultural Sciences, 2024)
The effectiveness of various molecules, including spinetoram 11.7 sc and flupyradifurone 200 sl, along with chemical checks like emamectin benzoate 5 sg and deltamethrin 2.8 ec, was investigated for controlling bruchid infestation and preserving seed quality during ambient storage at University of Agricultural Sciences, Bengaluru, Karnataka (2021–22). After 9 months, spinetoram 11.7 sc at 25.6 mg/kg seeds (T3) demonstrated outstanding results compared to the control (T9). Treatment T3 exhibited the highest 100-seed weight (5.28 g), lowest seed moisture (9.64%), and the highest germination rate (82%). Additionally, treatment T3 showed maximum shoot length, root length, mean seedling length, and mean seedling dry weight. The electrical conductivity (EC) of seed leachate was significantly lower in T3 (834 µS/cm) treatment, highlighting its superiority. Spinetoram 11.7 sc also excelled in dehydrogenase activity, protein content and total soluble sugars, indicating its positive impact on seed quality. Bruchid infestation significantly reduced in treatment T3 (1.42%), while untreated seeds exhibited the highest seed damage (16.50%). Teatment T3 recorded the fewest live and dead bruchids per 400 seeds, as well as the lowest seed infection. Compared to other treatments, spinetoram 11.7 sc at 25.6 mg/kg seeds emerged as the most effective in controlling bruchids and maintaining superior seed quality, as reflected in its highest B:C ratio. Overall, this research suggests that spinetoram can be a highly effective solution for bruchid control and seed quality preservation in blackgram during storage.